2010
DOI: 10.1016/j.ejpain.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Evoked potentials generated by noxious stimulation in the human infant brain

Abstract: While human infants can display distinctive behavioural and physiological spinal cord and brainstem responses to noxious stimulation, it is not known whether cortical neurons are specifically activated by noxious stimuli in newborns. Here, using a novel approach to time-lock an EEG recording to a clinically required heel lance, we show the presence of a distinct nociceptive-specific potential in newborn infants (35-39 weeks postmenstrual age). The potential can be observed in single trials in the central elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
196
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(217 citation statements)
references
References 31 publications
18
196
0
3
Order By: Relevance
“…In contrast, we were unable to record APs from DH neurons prior to 16 WG, which may indicate differences in the development of electrical activity in the DH and VH of the human fetal spinal cord. These findings are consistent with classical anatomical (Okado et al 1979(Okado et al , 1981Ray and Wadhwa 1999;Sarnat et al 1998) and clinical studies (de Vries et al 1985;Slater et al 2010b) that indicate functional connectivity develops earlier within motor circuits compared with those in the DH involved in processing tactile and nociceptive information.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, we were unable to record APs from DH neurons prior to 16 WG, which may indicate differences in the development of electrical activity in the DH and VH of the human fetal spinal cord. These findings are consistent with classical anatomical (Okado et al 1979(Okado et al , 1981Ray and Wadhwa 1999;Sarnat et al 1998) and clinical studies (de Vries et al 1985;Slater et al 2010b) that indicate functional connectivity develops earlier within motor circuits compared with those in the DH involved in processing tactile and nociceptive information.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, the "pain experience" requires a functional ascending pain pathway, whereby peripherally generated noxious signals reach the spinal cord and are then relayed to the somatosensory cortex. Electrophysiological studies on newborn humans have demonstrated cortical potentials in response to noxious procedures that break the skin (Slater et al 2010b). These data suggest most components of the pain neuroaxis are fully formed at birth.…”
Section: Spinal Reflexes and Pain Responses In The Human Fetusmentioning
confidence: 95%
“…Its perception is multidimensional and varies in quality, intensity, duration, location and symbolic image, according to the characteristics of each individual. Factors such as age, previous painful experience, cognition, learning, psychomotor stage, use of sedatives and analgesics and family conditions can modify the expression of pain, and this makes it more difficult to quantify and qualify in healthy term and premature neonates 27,28,32 . One of the arguments to the claim that the newborn cannot perceive pain is the cortical immaturity.…”
Section: Pain and Prematuritymentioning
confidence: 99%
“…Recently, the field has turned to exciting new evidence of pain-induced activity in the brain of human infants, which offers real insight into how pain is processed at higher levels of the newborn CNS (Slater et al 2006(Slater et al , 2010cFabrizi et al 2011;Williams et al 2015;Goksan et al 2015). This has provided previously unknown information about how much noxious information reaches the newborn brain and has opened the door to new research into the functional development of early nociceptive circuits in the somatosensory cortex and other brain areas in man.…”
Section: Introductionmentioning
confidence: 99%